Hepatic metastatic paraganglioma 12 years after retroperitoneal paraganglioma resection: a case report - Zhao-Ru Dong (BMC Gastroenterology, 2019)
Abstract Background Paragangliomas, also known as chemodectomas, are rare tumors arise from chemoreceptor tissue, and most commonly locate at the bifurcation of the common carotid, the jugular foramen, aortic arch, and retroperitoneum. Paragangliomas generally are considered to be benign tumors, and rarely produce local or distant metastases. Metastasis to liver is extremely rare. Case presentation We report the case of a 39-year-old woman, who had undergone resection of a retroperitoneal paraganglioma at her local hospital for 12 years. She was referred to our hospital for further evaluation of a hepatic mass, which was misdignosed as hepatocellular carcinoma (HCC) and was treated by transarterial chemoembolization (TACE) in the local hospital 6 years ago. At admission, CT scan revealed a huge hypervascular mass with many feeding arteries, almost the same size as 5 years ago. Ultrasound-guided biopsy of the liver tumor was performed and immunohistochemical examination confirmed the diagnosis of hepatic metastatic paraganglioma. Though liver metastasis failed to achieve complete response or partial response to TACE treatment, it remained stable without progression during the 7-year follow-up. Conclusion Paragangliomas are slow growing tumors and metastasis may develop decades after resection of the primary lesion. Long-term follow-up is necessary, and curative or palliative treatment should be considered to control symptoms, improve life quality, reduce complications and prolong survival.